Clinical Profile and Short-Term Outcome of Children Admitted with COVID-19 During the Second Wave in a Tertiary Care Centre in Kerala - John, Sangeetha Rachel; A S, Ajith Krishnan; S, Bindu (Journal of College of Medical Sciences-Nepal, 2025)
Background COVID-19, caused by SARS-CoV-2, emerged in Wuhan, China in December 2019 and was declared a pandemic by the WHO on March 11, 2020. In India, the second wave occurred between March and June 2021, affecting children across all age groups with presentations ranging from mild symptoms to severe multisystem involvement. This study describes the clinical profile and short-term outcomes of children admitted with COVID-19 in a tertiary care center in Kerala. Methods A descriptive study was conducted among 246 children aged 1 month to 13 years, admitted to the COVID-19 isolation ward between May and July 2021, with laboratory confirmed COVID-19. Socio-demographic details, clinical features, and short-term outcomes were analysed. Results Among the 246 children studied, aged 1 month to 13 years, the median age was 48 months (IQR: 16–99 months), with a slight male predominance. A positive contact history was reported in 81% (n=200), and 28% (n=70) had severe disease. Common symptoms included fever (67%), cough (27%), and seizures (27%). The mortality rate was 0.8%. Comorbidities were present in 38% (n=93), with these children requiring significantly more respiratory support (p<0.001, OR=6.1). Neurological comorbidities were notably associated with severe disease (p<0.001, OR=4.6). Conclusions Children admitted with COVID-19 presented with a wide clinical spectrum, from mild illness to severe multi system involvement. The disease affected all age groups, with a slight male preponderance. Children with neurological comorbidities exhibited more adverse outcomes.